3D numerical simulation of thermal fatigue damage in wedge specimen of AISI H13 tool steel. (July 2017) - Qayyum, Faisal; Kamran, Atif; Ali, Asghar; Shah, Masood
Graphical abstract: Highlights: Accurate 3D FE numerical simulation model was developed. Actual boundary conditions and Temperature dependent material data was used. Damaging stresses produced in wedge specimen during thermal fatigue were analyzed. Crack initiation sites and limiting crack length were indentified. The model is helpful in predicting failure in complex components due to thermal fatigue. Abstract: Thermal fatigue loading is a major failure mechanism in machinery operating at high temperatures. Numerical modeling of this phenomena helps in better understanding of crack propagation governing factors, which eventually helps in avoiding catastrophic failures. In this research numerical simulation model for crack propagation in a 3D wedge of AISI H13 tool steel has been developed. Thermal profiles incorporated in the model were taken from actual experimentation. Real time temperature dependent material data was used. Contour integral technique was employed to simulate the behavior of material with increase in crack lengths. Total 11 models with different crack lengths were simulated to observe the behavior of crack length on J-integral, compressive and tensile stresses and Crack Mouth Opening Displacement (CMOD). 3D graphs of J-integral gives an insight of how thermal fatigue cracks behave in bulk. The simulation results correlate well with experimental observations. Results show a significant drop in stresses and j-integral values after certain crack length, which eventually results in crack arrest.